Rolling microneedle electrode array (RoMEA) empowered nucleic acid delivery and cancer immunotherapy. (February 2021) - Yang, Tongren; Huang, Dong; Li, Chunhui; Zhao, Deyao; Li, Junshi; Zhang, Mengjie; Chen, Yufeng; Wang, Qining; Liang, Zicai; Liang, Xing-Jie; Li, Zhihong; Huang, Yuanyu
Graphical abstract: Highlights: siRNA therapy shows encouraging potential in disease treatment, but is hampered by insufficient delivery. Combination of electroporation and microneedle constitutes a promising strategy, but it is quite challenging. Rolling microneedle electrode array (RoMEA) was engineered by employing microfabrication technology in this study. Efficiency restoration of immune surveillance and tumor killing were achieved by RoMEA-electroporated anti-PD-L1 siRNA. RoMEA exhibited excellent safety profiles in vivo . Abstract: Topical administration of siRNA, a clinically approved promising therapeutic modality, represents a much more transformative approach for drug development, compared to intravenous injection. To implement an efficient and extensive siRNA therapy in vivo, we engineered a rolling microneedle electrode array (RoMEA), which utilizes parallel circular blades with microneedle arrays on edge as electrodes. RoMEA integrates close-spaced microneedle electrodes and rolling structure to allow low-damage and large-area siRNA transfection. Upon applying RoMEA, regular micropores were established, efficient siRNA delivery and gene silence were achieved. In addition, employments of siRNA targeting programmed death-ligand 1 (PD-L1) alone, or combined with anti-programmed death-1 (PD-1) antibody or immunoadjuvant of CpG2395, in two tumor xenograft murine models demonstrated that proposed strategies restored efficient T cell immune response, conferring significant tumor growth inhibition with excellent safety profiles. RoMEA constitutes an unprecedented and ingenious clinic solution to large-area local delivery of nucleic acid for cancer immunotherapy.